Reconstructing the fictional character of Fourteenth Daughter Xin (Xin Shisi Niang) in the English Translation of Liaozhai Zhiyi - Yi, Shuihan; Ng, Chwee Fang; Abdul Halim, Hazlina (Academy Publication, 2025)
Fourteenth Daughter Xin (Xin Shisi Niang) is one of the unusual tales in the anthology Liaozhai Zhiyi by Chinese novelist Pu Songling. The characterization of Fourteenth Daughter Xin, crafted to portray both the character development of the memorable female protagonist and the story’s structure, contains numerous Chinese literary and cultural elements that present challenges in English translation. This study, based on a systematic examination of the original Liaozhai Zhiyi and its complete English version, aims to investigate how the translator reconstructs Fourteenth Daughter Xin’s character image in English renderings. Through analysis of Fourteenth Daughter Xin’s appellation, appearance, speech, and action, the findings reveal that the translator enhances emotional descriptions, emphasizes the elegance and beauty of Fourteenth Daughter Xin, and simplifies some action descriptions through omissions and adaptations. It can be observed that the translator tends to preserve cultural nuances closely while effectively conveying the overall characterization of Fourteenth Daughter Xin. This research aspires to serve as a reference for the English translation of literary fictional characters, facilitating the international dissemination of ancient Chinese literature.